System Dynamic Modeling for Terrorism Considering Infiltration - Hennie Husniah,*, R. A. R. Harry Anwar, Deni Haspada, Davidescu C. Victoria, Asep K. Supriatna (International Journal of Advanced Science and Technology, 2020)
This article aims to show the development of a terrorism model through a dynamic system approach in a human population. The authors consider that the underlying population is divided into three categories, namely terrorists, pacifists, and those who are easily influenced by both terrorist and pacifist propaganda. The dynamic behavior of the three subpopulations is represented using three differential equations. These differential equations show the growth of the three subpopulations. The model takes into account the impact of direct military / police interventions in order to reduce the terrorist subpopulation, and nonviolent, persuasive interventions to influence vulnerable people to be pacifists. The authors also look at the effect of infiltration as another intervention on the terrorist population. Moreover, the authors present numerical examples to illustrate system behavior and some important features resulting from the proposed dynamic model. One of the important features is that the effect of military / police interventions is significantly affected by the characteristics of the system, which is represented by the values of the parameters in the model. The effectiveness of terrorists to attract susceptibles to become new members, which is often called as the force of influence, is among the parameters that influences the effect of the intervention. We simulate various scenarios for different values representing low, medium, and high force of influence. A broad insight into how to design appropriate terrorism management in a scientific way is also presented.